Challenges and Opportunities: Building Archival Infrastructure for ONE DATA - Mohamad Pandu Ristiyono; Miih Saropah (Yayasan Putra Adi Dharma, 2023)
The importance of records infrastructure in Indonesia's ONE DATA initiative, focusing on several key aspects. Records infrastructure is the foundation that supports integrity, better public services, transparency and accountability in government data management. Key challenges faced in building a solid records infrastructure include technical issues, financial constraints, legal and policy issues, the need for skilled human resources, variable data quality, and strict privacy policies. However, there are opportunities that can be capitalised on, such as technological innovation, strategic partnerships, and long-term benefits in the form of efficiency and better public services. ONE DATA also highlights implementation and how a strong records infrastructure can impact data integration, accuracy and benefits to public services. Barriers to building a records infrastructure include limited resources, data ownership, data quality, privacy policies, data consistency and standards, and awareness and compliance. The conclusion of this article is that, while there are many challenges to overcome, a strong archive infrastructure can support the vision of ONE DATA. Strategic investment, strong leadership, collaboration, education, and continuous evaluation are necessary to achieve this goal and bring significant benefits to society, innovation, and better decision-making. This means that Indonesia is moving towards an era of integrated data.